Design of buckling restrained steel braces using application programming interface between simulation and discrete optimization. (September 2022) - Tunca, Osman
Abstract: In this study, buckling restrained braces (BRBs) are optimized through application programming interface between simulation and discrete optimization. It is aimed to maximize the energy dissipation capacity of BRBs considering the American Institute of Steel Construction (ANSI/AISC 341). Unlike other studies, BRBs modeled in the finite element packaged software are directly linked to optimization algorithms. So, the geometric and material nonlinearities are also considered. Harmony Search Algorithm (HSA), which simulates the improvisation musician performances in finding pleasing harmony, and Black Widow Optimization Algorithm (BWOA), which imitates inimitable paring attitude of black widow spiders, are taken as the optimizer tools of this study. They encoded in Microsoft Visual Basic programming language. Initially, the algorithmic performances of the HSA and BWOA are compared and evaluated on two benchmark structural engineering design problems. Afterward, two different shaped BRBs are modeled in a finite element analysis (FEA) based software, namely ANSYS Workbench. Then, the obtained simulations are integrated with the HS and BWO algorithms throughout the application programming interface without identification of complex objective function and design constraints in formulations. These are directly calculated by ANSYS Workbench over very simple formulas. So, the attained optimum designs of BRBs are investigated with a new approach. Furthermore, in order to see the supreme algorithmic performances of the HSA and BWOA, all benchmark and BRB design problems are solved so-called well-established conventional standard Genetic Algorithm (sGA). Eventually, the proposed novel design methodology gives opportunity and eases to the designers since it provides convenience in solving complicated problems having nonlinear objective function and design constraints that are tiresome to encode.